Precarious encounters with urban life: The city/psychosis nexus beyond epidemiology and social constructivism - Söderström, Ola (My University, 2019)
The article analyses the specific sense of precarity experienced in cities by persons living with a diagnosis of schizophrenia. It aims to bring a social science perspective on precarity as embodied affect into conversation with perspectives on psychosis in the life sciences. To do so the article focuses on two moments in an interdisciplinary research process involving psychiatrists, linguists and geographers. The first is an epistemic moment describing the co-design of a research laboratory across the social and the life sciences to study participants' precarious encounters with urban situations. The second is an ontological moment discussing the results of co-experimentation across disciplines in the research team. It shows how collaboration within the team led to a redefinition of our respective analytical categories and discusses empirical findings concerning factors of urban stress and protection for persons living with a diagnosis of schizophrenia. The conclusion situates the socio-natural analysis of urban precarity developed in the paper within broader contemporary discussions on the study of bio-social entanglements. Arguing for epistemological plurality and ontological contamination, the paper is both a methodological contribution to contemporary debates in geographies of health and a contribution to studies of urban precarity.
Keywords: Schizophrenia; Video-analysis; Interdisciplinarity; Psychiatry; Geography; Ethnomethodology; Urbanity